FACILITIES PLANNING WORKSHOP FOR BLASTING SUPPORT THE ACTIVITY OF DEVELOPMENT AND REPAIR SHIP IN PT. JASA MARINA INDAH UNIT II - Samuel, Samuel; Budi Santosa, Ari Wibawa (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2010)
Blasting in the process of planning the workshop production of new building and ship repair to play a role in providing blasting and paint on the block that will be of erection. As a result of blasting workshop facilities that do not have resulted in low production capacity that can be achieved by this workshop, namely three block ships per month. Capacity blasting and paint shop in this low resulted in low productivity process stage (stage) the previous workshops which of course result in a decrease in vessel productivity in general.                 In penelitiaan aims to plan for blasting and paint shop facility which has been adjusted to the planned production capacity of PT. JASA MARINA INDAH II units.                 In this study it - thing to note is to understand the data - the data field for research conducted in terms of both technical and economic terms, with the blasting and paint shop facilities on the construction or repair of ships that have been planned, then the effectiveness of the work and production flow at. Jasa Marina Indah II units can be known.                 Based on the analysis and calculation of both technical and economical it can be identified by the workshop on the process of blasting Blasting efficiency is obtained for 2.55 hours, at 10.16 hours during the painting process, while economical in terms of labor costs can be reduced blasting cost is Rp.930000    for          paint       and         Rp.1.23million